The Court Ruling Regarding Gender Change in Human Rights Law - Fernando J. M. M. Karisoh; Caecilia J. J. Waha; Jemmy Sondakh; Emma V. T. Senewe (AIBPM Publisher, 2021)
The phenomenon of gender change in Indonesia shows that many people want to change their gender. This study aims to examine and analyze legal arrangements in the field of human rights regarding gender change, the implementation of court decisions in Indonesia regarding gender change and the effect of the formation of laws and regulations that specifically regulate gender change on court decisions in Indonesia. Normative research carried out by means of law, conceptual and case approaches. The results showed international agreements and national legislation have not specifically regulated gender change. The court ruling is based on consideration of the results of the medical examination and legal considerations. The establishment of legislation in particular can strengthen court ruling.